Clinical and radiographic outcomes with L4–S1 axial lumbar interbody fusion (AxiaLIF) and posterior instrumentation: a multicenter study - Tobler WD (Dove Medical Press, 2013)
William D Tobler,1 Miguel A Melgar,2 Thomas J Raley,3 Neel Anand,4 Larry E Miller,5 Richard J Nasca6 1Department of Neurosurgery, University of Cincinnati College of Medicine, Mayfield Clinic, and The Christ Hospital, Cincinnati, OH, USA; 2Department of Neurosurgery, Tulane University, New Orleans, LA, USA; 3Advanced Spine and Pain, Arlington, VA, USA; 4Spine Trauma, Minimally Invasive Spine Surgery Spine Center, Cedars-Sinai Medical Center, Los Angeles, CA, USA; 5Miller Scientific Consulting, Inc, Arden, NC, USA; 6Orthopaedic and Spine Surgery, Wilmington, NC, USA Introduction: Previous studies have confirmed the benefits and limitations of the presacral retroperitoneal approach for L5–S1 interbody fusion. The purpose of this study was to determine the safety and effectiveness of the minimally invasive axial lumbar interbody approach (AxiaLIF) for L4–S1 fusion. Methods: In this retrospective series, 52 patients from four clinical sites underwent L4–S1 interbody fusion with the AxiaLIF two-level system with minimum 2-year clinical and radiographic follow-up (range: 24–51 months). Outcomes included back pain severity (on a 10-point scale), the Oswestry Disability Index (ODI), and Odom's criteria. Flexion and extension radiographs, as well as computed tomography scans, were evaluated to determine fusion status. Longitudinal outcomes were assessed with repeated measures analysis of variance. Results: Mean subject age was 52 ± 11 years and the male:female ratio was 1:1. Patients sustained no intraoperative bowel or vascular injury, deep infection, or neurologic complication. Median procedural blood loss was 220 cc and median length of hospital stay was 3 days. At 2-year follow-up, mean back pain had improved 56%, from 7.7 ± 1.6 at baseline to 3.4 ± 2.7 (P < 0.001). Back pain clinical success (ie, ≥30% improvement from baseline) was achieved in 39 (75%) patients at 2 years. Mean ODI scores improved 42%, from 60% ± 16% at baseline to 35% ± 27% at 2 years (P < 0.001). ODI clinical success (ie, ≥30% improvement from baseline) was achieved in 26 (50%) patients. At final follow-up, 45 (87%) patients were rated as good or excellent, five as fair, and two as poor by Odom's criteria. Interbody fusion observed on imaging was achieved in 97 (93%) of 104 treated interspaces. During follow-up, five patients underwent reoperation on the lumbar spine, including facet screw removal (two), laminectomy (two), and transforaminal lumbar interbody fusion (one). Conclusion: The AxiaLIF two-level device is a safe, effective treatment adjunct for patients with L4–S1 disc pathology resistant to conservative treatments. Keywords: AxiaLIF, axial presacral fusion, interbody, outcomes, two-level fusion